Who Chose the Gospels? probing the great Gospel conspiracy - Hill, Charles E. (Charles Evan), 1956- (Oxford ; New York : Oxford University Press, 2010)
The Bible contains four Gospels which tell the story of Jesus of Nazareth. And yet, many more Gospels once existed. Who, then, determined which Gospels would, for the next two thousand years, serve as the main gateways to Jesus and his teaching? Recent books and films have traced the decision to a series of fourth-century councils and powerful bishops. After achieving victory over their rivals for the Christian name, these key players, we are now told, conspired to 'rewrite history' to make it look like their version of Christianity was the original one preached by Jesus and his apostles.
Introduction : drowning in a sea of Gospels -- The proof is in the papyri? : Gospel bestsellers from Egyptian garbage dumps -- Silencing the Bishop, part I : the lonely Irenaeus -- Silencing the Bishop, part II : the ugly Irenaeus -- Irenaeus' 'co-conspirators' : a teacher, a preacher, and a canon-list maker -- 'Packaging" the Gospels : of harmonies, synopses, and codices -- Preaching and teaching the Gospels : Justin Martyr and the Apostles' memoirs -- Justin's 'co-conspirators' : the Gospels as public documents -- Some 'proto-conspirators' : two forgers and an apologist -- Some 'co-proto-conspirators' : the Apostolic Fathers -- The search for an 'arch-conspirator' : a bishop, an elder, and an elderly Apostle -- Who chose the Gospels? -- Appendix : dates of the earliest manuscripts of the canonical Gospels.
Description based upon print version of record.
Includes bibliographical references (p. 256-288) and index.
Keywords: Bible. -- Canon; Bible. N.T. Gospels -- Canon; Bible. N.T. Gospels -- Criticism, interpretation, etc; Bible. N.T. Gospels -- History; Religion; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books